Blurring the lines a profile of state and local police enforcement of immigration law using the National Crime Information Center database, 2002-2004. - Gladstein, Hannah; Migration Policy Institute; New York University. School of Law. (2005)
In almost 9,000 cases from 2002 to 2004, police officers checking the names of individuals stopped or detained against records in the nation's main criminal database received an initial "hit" for an immigration violation that, upon further investigation, the Department of Homeland Security could not confirm. The rate of false positives was 42 percent overall, and some individual law enforcement agencies had error rates as high as 90 percent.
Viewed on (Mar. 8, 2006).
Keywords: Illegal aliens -- Government policy -- United States; Law enforcement -- United States